Pseudo-Weak-R0 Algebras - Yong Lin Liu; Xiaobo Cai (The Scientific World Journal)
A positive answer to the open problem of Iorgulescu on extending weak-R0 algebras and R0-algebras to the noncommutative forms is given. We show that pseudo-weak-R0 algebras are categorically isomorphic to pseudo-IMTL algebras and that pseudo-R0 algebras are categorically isomorphic to pseudo-NM algebras. Some properties, the noncommutative forms of the properties in weak-R0 algebras and R0-algebras, are investigated. The simplified axiom systems of pseudo-weak-R0 algebras and pseudo-R0 algebras are obtained.